2018
DOI: 10.3324/haematol.2017.185397
|View full text |Cite
|
Sign up to set email alerts
|

Maternal embryonic leucine zipper kinase inhibitor OTSSP167 has preclinical activity in multiple myeloma bone disease

Abstract: Multiple myeloma bone disease is characterized by an uncoupling of bone remodeling in the multiple myeloma microenvironment, resulting in the development of lytic bone lesions. Most myeloma patients suffer from these bone lesions, which not only cause morbidity but also negatively impact survival. The development of novel therapies, ideally with a combined anti-resorptive and bone-anabolic effect, is of great interest because lesions persist with the current standard of care, even in patients in complete remis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
(53 reference statements)
3
5
0
Order By: Relevance
“…Several studies have reported that MELK acts as an oncogene in many kinds of tumours from multiple systems. [33][34][35][36][37][38] In this study, we cycle, DNA repair and replication, which was similar to previous reports. 6,26,33,[39][40][41][42][43] Next ous studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several studies have reported that MELK acts as an oncogene in many kinds of tumours from multiple systems. [33][34][35][36][37][38] In this study, we cycle, DNA repair and replication, which was similar to previous reports. 6,26,33,[39][40][41][42][43] Next ous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported that MELK acts as an oncogene in many kinds of tumours from multiple systems . In this study, we confirmed the oncogenic role of MELK in bladder tumorigenesis and elucidated for the first time the regulatory mechanism of MELK inhibition in BCa cells by bioinformatics analysis as well as in vitro/ in vivo investigation.…”
Section: Discussionsupporting
confidence: 79%
“…Osteoclast differentiation and resorptive activity were studied as previously described 13 , 14 . Briefly, RAW264.7 cells were initially seeded in αMEM medium supplemented with recombinant murine sRANKL (Peprotech, London, UK) at day 1.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo experiments were performed using the 5TGM.1 murine model of myeloma as previously described. 19 These experiments were approved by the ethical committee for animal experiments of the University of Li ege (ULg license #16-1897). Treatment was initiated 1 day after the injection of myeloma cells (9-week-old female mice were injected i.v.…”
Section: In Vivo Studiesmentioning
confidence: 99%